(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Digital dictionaries have transformed language learning by offering quick and interactive access to definitions, translations, and other language resources. This study examines whether digital dictionaries improve learning efficiency for university students compared to traditional print dictionaries. Results reveal that digital dictionaries significantly enhance the speed and convenience of vocabulary acquisition, with additional benefits for retention and engagement.The digital age has fundamentally changed how students access and engage with learning materials. Among these resources, digital dictionaries have become essential for language learners, offering a faster and more interactive experience than traditional print dictionaries. They enable students to access definitions, translations, pronunciation guides, and contextual usage examples with ease. Despite their widespread use, research on the actual effectiveness of digital dictionaries in improving language learning outcomes remains limited. This article explores the impact of digital dictionaries on university students’ language learning efficiency, comparing digital and print dictionary usage to determine which method better supports vocabulary acquisition and retention.